Devario deruptotalea, a new species of cyprinid fish from Manipur, India (Teleostei: Cyprinidae) - Ramananda, Yumnam; Vishwanath, Waikhom (Zootaxa, 2014)
Devario deruptotalea, a new cyprinid fish, is described from Dutah Stream, a tributary of the Yu River (Chindwin drainage) in Manipur, India. It is distinguished from all its congeners by a unique colour pattern consisting of the following combination of pigmented elements: 4‒6 dark brown irregularly shaped and arranged bars that are partly confluent with adjacent bars at different levels on the anterior one-third of the side of the body, followed by three distinct dark brown stripes posteriorly, a P stripe that is darker and about twice as broad as other stripes and extending to the tip of the median caudal-fin rays.